2012
DOI: 10.1155/2012/753472
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Evaluation of Symptomatic Patients following Bariatric Surgery: A Literature Review

Abstract: Obesity is an epidemic in our society, and rates continue to rise, along with comorbid conditions associated with obesity. Unfortunately, obesity remains refractory to behavioral and drug therapy but has shown response to bariatric surgery. Not only can long-term weight loss be achieved, but a majority of patients have also shown improvement of the comorbid conditions associated with obesity. A rise in the use of surgical therapy for management of obesity presents a challenge with an increased number of patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…72 The presence of H. pylori, as part of chronic active gastritis, on preoperative endoscopy, has been documented in 85.5% of patients, in a study on morbidly obese Saudi patients undergoing bariatric surgery. 73 It was speculated that the high prevalence could have been attributed to several factors, including sanitation and socio-economic factors. We found a similarly high presence of H. pylori in our black patients, the reason for which remains unclear.…”
Section: Aspiration Pneumonia 1 Pneumoniamentioning
confidence: 99%
“…72 The presence of H. pylori, as part of chronic active gastritis, on preoperative endoscopy, has been documented in 85.5% of patients, in a study on morbidly obese Saudi patients undergoing bariatric surgery. 73 It was speculated that the high prevalence could have been attributed to several factors, including sanitation and socio-economic factors. We found a similarly high presence of H. pylori in our black patients, the reason for which remains unclear.…”
Section: Aspiration Pneumonia 1 Pneumoniamentioning
confidence: 99%
“…The majority of late postoperative bleedings are intraluminal [5,7]. They may develop several months and even years after surgery, being most commonly caused by ulcers in gastrojejunoanastomosis or the remnant stomach and duodenum [1,4,6,7]. In late postoperative period about 20% of patients develop ulcers [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…Like any other surgical intervention, RYGB is associated with possible complications and many of them may become life threatening. Postoperative bleeding is one of such complications, its prevalence being cited as 1-4% [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this multitude of possible findings, a normal gastric endoscopy has been consistently reported as the most common post-operative endoscopic finding in these patients (8,10,14,22) . Despite these findings, to our knowledge none of these previous studies has reported co-occurring patterns.…”
Section: Long-term Postoperative Endoscopic Findings After Gastric Bymentioning
confidence: 91%